Using preoperative three‐dimensional endoanal ultrasound to determine operative procedure in patients with perianal fistulas. (17th February 2020) - Mantoo, S.; Mandovra, P.; Goh, S.
Abstract: Aim: Accurate preoperative identification of perianal fistula tracts and internal openings can facilitate the choice of surgical procedure and may lead to improved healing rates. Our aim was to explore the effectiveness of three‐dimensional endoanal ultrasound (3D‐EAUS) in determining the type of perianal fistula and planning operative management. Method: This was a cohort longitudinal study. Patients with perianal fistulas from January 2017 to January 2018 who underwent 3D‐EAUS and subsequent surgery were included. Intra‐operative findings were considered as standard for comparison with clinical examination and 3D‐EAUS findings. The primary outcome measure was to evaluate the concordance between 3D‐EAUS and intra‐operative findings and the secondary outcome measure was healing rates. Results: Sixty‐eight patients with a mean age of 43.1 ± 14.1 years were included. Twenty‐eight patients had inter‐sphincteric (41.2%) and 40 (14 high and 26 low) trans‐sphincteric fistulas (58.8%). 3D‐EAUS, clinical examination and intra‐operative exploration could predict the location of internal openings in 62/68 (91.2%), 48/68 (70.5%) and 56/68 (82.4%) patients, respectively. Hydrogen peroxide (H₂O₂)‐enhanced 3D‐EAUS accurately predicted the location of internal openings when compared with 3D‐EAUS without H₂O₂ (concordance K = 0.963, P = 0.05). High concordance rates were seen between intra‐operative and 3D‐EAUS findings on the type of perianal fistula. No significant difference was seen between the suggested surgical treatment based on 3D‐EAUS and the eventual surgical treatment ( P > 0.05). Study limitations were the small sample size and lack of randomization. Conclusion: 3D‐EAUS may be considered as a first‐line investigation for patients with perianal fistulas because of high concordance with intra‐operative assessment and facilitation of surgical planning.